BRIN's Position in Indonesian Research and Innovation Discourse: A Semantic Network Analysis of News Media Coverage 2022-2024 - Shiddiq Sugiono; Perdhani Yunia Putri; Purwadi Purwadi (FAKULTAS DAKWAH UIN SALATIGA, 2026)
As a newly established organization, BRIN needs to build institutional legitimacy in research and innovation performance, one of which is pursued through media coverage. However, this legitimacy can be distorted by media logic that prioritizes sensationalism and the dramatization of issues. BRIN's position within the discourse on research and innovation needs to be analyzed to understand the extent to which media coverage contributes to constructing its institutional legitimacy. This study aims to examine and test the semantic-structural similarity between the discourse on BRIN and that on research and innovation. The data were drawn from 5,716 articles published in Indonesia's top five news media outlets between 2022 and 2024. Semantic network analysis was employed to assess centrality and semantic similarity. The findings reveal significant fluctuations in the relationship between BRIN discourse and research and innovation discourse, illustrating the negotiation of institutional legitimacy through media representation. The weakening correlation observed in 2023 indicates the dominance of media logic, which prioritizes sensational and controversial aspects, generating representations that do not always align with BRIN's core institutional mission and suggesting a partial alignment between the discourse on BRIN and that on research and innovation.